Inside Chinese Theatre: Cantonese Opera in Canada - Rao, Nancy (Intersections)

(untitled) (Canadian University Music Society / Société de musique des universités canadiennes, 2018)
Opera theatre forms an important part of Chinese Canadian cultural history. Since first appearing in Victoria in the 1860s, Chinese theatres were woven into the community’s everyday life, performing Cantonese opera, the regional genre known to the majority of Chinese immigrants who came from the Pearl River Delta of southern China. A brief survey of historical city maps from the late nineteenth and early twentieth century shows their central role in Chinese Canadian community of the Pacific Northwest. Recent discovery of a Chinese theatrical company’s daily business receipts provides a window into the performance culture and daily operations of a Chinese theatre between 1916 and 1918 in Vancouver. This vibrant period of the 1910s paved the way for full-fledged theatre operation in the following decade that brought about a new era of Chinese opera performance in Canada.